2020
DOI: 10.1177/1055665620929247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Case Series of Syndromic and Nonsyndromic Cleft Lip and Palate in a Saudi Arabian Neonatal Population

Abstract: Objective: To report clinical case series of cleft lip with or without palate (CL/P) and to estimate the prevalence of infants with CL/P who were syndromic or nonsyndromic. Design: This is a clinical case series study of CL/P among live births in the maternity hospital. Setting: The study was carried out in Maternity and Children Hospital, Najran between January 2013 and December 2016. Materials and Methods: Sex and clinical presentation of CL/P were collected from the medical records of live births. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In Mexico, such prevalence at birth rates depicted an prevalence at birth of 0.54 per 1000 live births during 2010-2015 20 ; 1.00 per 1000 live births during 2008-2010: 2.8 per 1000 live births during 2009-2016. 7,21 In Saudi Arabia, a prevalence at birth rate of 0.65 per 1000 live births was reported 22 ; in Iran, 1.9 per 1000 live births 23 ; and in Thailand, 1.44 per 1000 live births. 24 The variability in estimates may be due to multiple causes, including different methods, and racial and environmental differences in populations.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, such prevalence at birth rates depicted an prevalence at birth of 0.54 per 1000 live births during 2010-2015 20 ; 1.00 per 1000 live births during 2008-2010: 2.8 per 1000 live births during 2009-2016. 7,21 In Saudi Arabia, a prevalence at birth rate of 0.65 per 1000 live births was reported 22 ; in Iran, 1.9 per 1000 live births 23 ; and in Thailand, 1.44 per 1000 live births. 24 The variability in estimates may be due to multiple causes, including different methods, and racial and environmental differences in populations.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated cleft palate is more common in women than in men due to several reasons including women having a development period of a prone palate that is one week longer than men and sex hormone in women in triggers cleft palate. 4,5,10,11 From this study the highest percentage was found in type III (38%), then followed by Veau type II (32%). This is in line with research by Emodi et al ( 2022) who conducted research in Israel that report from 258 patient's higher incidence was Veau II and III.…”
Section: Accompanying Syndromesmentioning
confidence: 49%
“… 50 Other risk factors reported from the observational studies were parental smoking, vitamin deficiencies, and lack of intake of folic acid during pregnancy. Studies conducted by Aljohar et al, 22 Aziza et al, 23 Sabbagh et al, 27 Moshref et al, 30 and Alyami et al 32 reported that the prevalence of OFC is higher among the male population in comparison with the female. These findings were contrary to the findings of the study reported by Ravichandran et al, 24 where the prevalence was higher among females in comparison with males.…”
Section: Discussionmentioning
confidence: 97%